Analisis Dampak Sistem Presidential Threshold dalam Pemilihan Presiden dan Wakil Presiden di Indonesia Terhadap Inklusivitas Politik dan Representasi Demokratis - Nugroho, Dwi Wahyu (Proceedings Series on Social Sciences & Humanities, 2024)
Article 222 of Law Number 17 of 2017 concerning Presidential and Vice Presidential Elections states that "Candidate pairs are proposed by political parties or combinations of political parties participating in the election who meet the requirements to obtain seats of at least 20% of the total number of seats in the DPR or obtain 25% of the valid national votes in election of members of the DPR. With these regulations there are inconsistencies, on the one hand this country adheres to democracy, but on the other hand there are restrictions on the rights of citizens who wish to run for president and/or vice president. Research on the presidential threshold system is important to understand its impact on the political system and democracy in Indonesia. So that we can understand how this system influences community political participation, the diversity of presidential and vice presidential candidates, and the representation of community interests. The method used is normative legal research. These provisions reduce political inclusivity by limiting the variety of options for voters and restricting access for various groups of society. And influence democratic representation by suppressing votes for minority candidates or those representing special interests.